First line therapy in stage IV BRAF mutated colorectal cancer - Fausto Petrelli; Maria Antista; Lorenzo Dottorini; Alessandro Russo; Marcella Arru; Roberta Invernizzi; Mariangela Manzoni; Chiara Cremolini; Alberto Zaniboni; Ornella Garrone; Gianluca Tomasello; Michele Ghidini (Heliyon, 2024)
Introduction: The molecular profile of colorectal cancer (CRC) plays a crucial role in understanding patient prognosis and treatment response. Within CRC, a distinct subgroup can be identified by the presence of the BRAF V600E mutation. This specific mutation, classified as Class I of BRAF mutations, is known to be associated with a poor prognosis and resistance to standard therapy. To determine the most effective treatment approach for this specific subgroup of CRC, we conducted a network meta-analysis (NMA) to compare various pharmacological interventions and evaluate their relative effectiveness in BRAF-mutated CRCs. Materials and methods: On July 31, 2023, we conducted a systematic search of PubMed, Cochrane Central Register of Controlled Trials, and Embase. The inclusion criteria were as follows: 1) reporting of outcomes in patients with BRAF-mutated CRC who underwent first-line chemotherapy; 2) reporting of survival information as hazard ratios (HR); and 3) publication in English. The data were combined using HRs for overall and progression-free survival (OS and PFS) using random-effects models. NMA was performed under the Bayesian framework, utilizing the GeMTC package. The relative rankings of the treatments were determined using SUCRA scores. Results: A total of 16 studies were included. When compared to standard chemotherapy (CT) doublets (such as FOLFOX or FOLFIRI), none of the comparison arms demonstrated a gain in OS. CT doublet + bevacizumab did not show significant superiority over either CT doublet alone or 5FU/capecitabine + bevacizumab. FOLFOXIRI and FOLFOXIRI + bevacizumab did not show superiority over any other treatment schedule that was compared. CT doublets + bevacizumab had the highest SUCRA score (0.87), followed by single-agent fluoropyrimidines + bevacizumab (0.61), and FOLFOXIRI (0.56). Regarding PFS, no regimen was found to be superior to the combination of CT doublet plus bevacizumab. However, FOLFOXIRI + bevacizumab + atezolizumab showed a tendency towards better results (HR = 0.26, 95 % CI 0.05–1.1). Conclusions: Our review suggests that a CT doublet with bevacizumab is the most favorable option for OS. However, a reasonable alternative could be a triplet CT without bevacizumab.